2011
DOI: 10.1042/bsr20100023
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant methylation of hMLH1 and p16INK4a in Tunisian patients with sporadic colorectal adenocarcinoma

Abstract: The methylation of CpG islands in the promoters is associated with loss of protein via repression of gene transcription. Several studies have demonstrated that tumour suppressor and DNA repair genes are often aberrantly hypermethylated in colorectal cancer. The present study was conducted to examine whether the methylation profile of p16INK4a and hMLH1 (human mutL homologue 1) promoters was associated with clinical features and patients' survival in CRC (colorectal carcinoma). Aberrant methylation of p16INK4a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 33 publications
1
9
0
1
Order By: Relevance
“…Full texts and data integrity were then reviewed and another 249 articles were excluded. Finally, 27 clinical cohort studies were included in this meta-analysis (Liang et al, 1999;Wiencke et al, 1999;Wang et al, 2001;Yi et al, 2001;Hibi et al, 2002;Nakayama et al, 2002;van Rijnsoever et al, 2002;Zou et al, 2002;Cheng et al, 2003;Norrie et al, 2003;Yang et al, 2003;Sanz-Casla et al, 2005;Iacopetta et al, 2006;Ishiguro et al, 2006;Li et al, 2006;Miranda et al, 2006;Krtolica et al, 2007;Mas et al, 2007;Nakayama et al, 2007;Kazama et al, 2008;Wettergren et al, 2008;Goto et al, 2009;Aoyagi et al, 2011;Miladi-Abdennadher et al, 2011;Iida et al, 2012;Sameer et al, 2012;Veganzones-de-Castro et al, 2012). The publication years of the eligible studies ranged from 1999 to 2012.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Full texts and data integrity were then reviewed and another 249 articles were excluded. Finally, 27 clinical cohort studies were included in this meta-analysis (Liang et al, 1999;Wiencke et al, 1999;Wang et al, 2001;Yi et al, 2001;Hibi et al, 2002;Nakayama et al, 2002;van Rijnsoever et al, 2002;Zou et al, 2002;Cheng et al, 2003;Norrie et al, 2003;Yang et al, 2003;Sanz-Casla et al, 2005;Iacopetta et al, 2006;Ishiguro et al, 2006;Li et al, 2006;Miranda et al, 2006;Krtolica et al, 2007;Mas et al, 2007;Nakayama et al, 2007;Kazama et al, 2008;Wettergren et al, 2008;Goto et al, 2009;Aoyagi et al, 2011;Miladi-Abdennadher et al, 2011;Iida et al, 2012;Sameer et al, 2012;Veganzones-de-Castro et al, 2012). The publication years of the eligible studies ranged from 1999 to 2012.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…A previous study reported significantly reduced recurrence-free survival and larger tumor volume with the MMR-deficient with MLH1 methylation group compared to the MMR proficient group, which is in agreement with results from the present study [ 28 ]. MLH1 promotor methylation has also been associated with adverse prognosis in cancer of other organs, such as the ovary and colon [ 29 , 30 ]. The prognostic significance in this study may suggest that MMR deficiency caused by somatic mutation (epigenetic silencing of MLH1 promotor) is an important cause of genomic instability, such as germline mutation in Lynch syndrome, which subsequently leads to aggressive behavior of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…MLH1 promoter hypermethylation has been reported in numerous types of tumors, including colorectal (33), gastric cancer (34) and EC (35). Previous studies have also reported that MLH1 hypermethylation may be associated with poor prognosis for patients with gastric (22), ovarian (36) and colorectal cancer (37), whilst studies on the prognostic value of MLH1 methylation in Han Chinese patients with EC or ESCC are scarce. The present study demonstrated that MLH1 promoter hypermethylation is a prognostic marker of ESCC in Chinese males.…”
Section: Discussionmentioning
confidence: 96%